2015
DOI: 10.1039/c4cc08838g
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transport machinery reconstituted in cell models

Abstract: Here we demonstrate the production of a functioning cell model by formation of giant vesicles reconstituted with the GLUT1 glucose transporter and a glucose oxidase and hydrogen peroxidase linked fluorescent reporter internally. Hence, a simplified artificial cell is formed that is able to take up glucose and process it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…8,15 The technique has since expanded the possibility to study complex lipid-protein interactions, 16,17 vesicles for applications in drug delivery 18 and use of vesicles as micro-reactors. 19,20 However no studies have reported multicompartment formation in vesicles using this methodology.…”
Section: Introductionmentioning
confidence: 99%
“…8,15 The technique has since expanded the possibility to study complex lipid-protein interactions, 16,17 vesicles for applications in drug delivery 18 and use of vesicles as micro-reactors. 19,20 However no studies have reported multicompartment formation in vesicles using this methodology.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent study employing channel proteins was conducted by Hansen et al Giant liposomes reconstituted with GLUT1 glucose transporter (GLUT) were assembled and their ability to encapsulate the enzyme tandem pair of GOx and HRP was evaluated. GLUT‐reconstituted giant liposomes were assembled employing a hydrogel‐assisted swelling procedure, and the ability of GLUT to allow for β ‐d ‐glucose transport was evaluated by monitoring the enzymatic activity of the system.…”
Section: Micro/nanosized Single‐compartment Enzymatic Reactorsmentioning
confidence: 99%
“…Different architectures that meet the aforementioned requirements have been considered for the design of artificial organelles, being liposomes and polymeric‐based systems the most advanced carriers both regarding structure but also functionality . Nonetheless, recently, other types of architectures made of inorganic materials such as silica are emerging as new systems for the construction of artificial organelles …”
Section: Introductionmentioning
confidence: 99%
“…For their reconstitution, solubilized membrane proteins can be dissolved in warm, molten agarose gels (Figure 2 B) (Hansen et al, 2013 , 2015 ; Gutierrez and Malmstadt, 2014 ). In this technique, precipitation of the detergents is prevented at a dilution below the cmc.…”
Section: Rehydration Of Protein-containing Agarosementioning
confidence: 99%
“…Upon rehydration of the lipids, protein-containing liposomes form from the surface of the protein-containing agarose. The proteins successfully used in this approach so far were aquaporin-Z, bacteriorhodopsin, and SoPIP2 (Hansen et al, 2013 ), as well as the glucose transporter GLUT1 (Hansen et al, 2015 ) and the human serotonin receptor 5-HT1A (Gutierrez and Malmstadt, 2014 ).…”
Section: Rehydration Of Protein-containing Agarosementioning
confidence: 99%